Mass Spectrometry Reveals Changes in MHC I Antigen Presentation After Lentivector Expression of a Gene Regulation System - Roland Vogel; Reem Al-Daccak; Oliver Drews; Jessy Alonzeau; Gabor Mester; Dominique Charron; Stefan Stevanovic; Jacques Mallet (Elsevier, 2013)
The rapamycin-inducible gene regulation system was designed to minimize immune reactions in man and may thus be suited for gene therapy. We assessed whether this system indeed induces no immune responses. The protein components of the regulation system were produced in the human cell lines HEK 293T, D407, and HER 911 following lentiviral transfer of the corresponding genes. Stable cell lines were established, and the peptides presented by major histocompatibility complex class I (MHC I) molecules on transduced and wild-type (wt) cells were compared by differential mass spectrometry. In all cell lines examined, expression of the transgenes resulted in prominent changes in the repertoire of MHC I-presented self-peptides. No MHC I ligands originating from the transgenic proteins were detected. In vitro analysis of immunogenicity revealed that transduced D407 cells displayed slightly higher capacity than wt controls to promote proliferation of cytotoxic T cells. These results indicate that therapeutic manipulations within the genome of target cells may affect pathways involved in the processing of peptide antigens and their presentation by MHC I. This makes the genomic modifications visible to the immune system which may recognize these events and respond. Ultimately, the findings call attention to a possible immune risk.